Conversão térmica e termocatalítica à baixa temperatura do óleo de girassol para obtenção de bio-óleo - Araújo, Aruzza Mabel de Morais (2011)
The use of biofuels remotes to the eighteenth century, when Rudolf Diesel made the first trials using peanut oil as fuel in a compression ignition engine. Based on these trials, there was the need for some chemical change to vegetable oil. Among these chemical transformations, we can mention the cracking and transesterification. This work aims at conducting a study using the thermocatalytic and thermal cracking of sunflower oil, using the Al-MCM-41 catalyst. The material type mesoporous Al-MCM-41 was synthesized and characterized by Hydrothermical methods of X-ray diffraction, scanning electron microscopy, nitrogen adsorption, absorption spectroscopy in the infrared and thermal gravimetric analysis (TG / DTG).The study was conducted on the thermogravimetric behavior of sunflower oil on the mesoporous catalyst cited. Activation energy, conversion, and oil degradation as a function of temperature were estimated based on the integral curves of thermogravimetric analysis and the kinetic method of Vyazovkin. The mesoporous material Al-MCM-41 showed one-dimensional hexagonal formation. The study of the kinetic behavior of sunflower oil with the catalyst showed a lower activation energy against the activation energy of pure sunflower oil. Two liquid fractions of sunflower oil were obtained, both in thermal and thermocatalytic pyrolisis. The first fraction obtained was called bio-oil and the second fraction obtained was called acid fraction. The acid fraction collected, in thermal and thermocatalytic pyrolisis, showed very high level of acidity, which is why it was called acid fraction. The first fraction was collected bio-called because it presented results in the range similar to petroleum diesel